2018
DOI: 10.1098/rsos.171395
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence theory of tissue failure: bulk and boundary effects

Abstract: The mortality rate of many complex multicellular organisms increases with age, which suggests that net ageing damage is accumulative, despite remodelling processes. But how exactly do these little mishaps in the cellular level accumulate and spread to become a systemic catastrophe? To address this question we present experiments with synthetic tissues, an analytical model consistent with experiments, and a number of implications that follow the analytical model. Our theoretical framework describes how shape, c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Finally, the relative importance of systemic aging to cell-level aging was recently determined to quantify the level of interactions between cells that lead to tissue-level failure. [86,87] Contrary to the in vivo situation, organoids or other techniques that simulate real tissues allow control of cellular level aging characteristics and cell-cell interaction strengths. Thus, through control of cellular-level damage and cell-cell distance in individual tissues, the systemic spread of failures from the cellular to the tissue level was demonstrated for the first time.…”
Section: The Tidis Theory Is Consistent With Lifetime Cancer Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the relative importance of systemic aging to cell-level aging was recently determined to quantify the level of interactions between cells that lead to tissue-level failure. [86,87] Contrary to the in vivo situation, organoids or other techniques that simulate real tissues allow control of cellular level aging characteristics and cell-cell interaction strengths. Thus, through control of cellular-level damage and cell-cell distance in individual tissues, the systemic spread of failures from the cellular to the tissue level was demonstrated for the first time.…”
Section: The Tidis Theory Is Consistent With Lifetime Cancer Risksmentioning
confidence: 99%
“…[86] In particular, an accelerated death rate was observed when cells were separated far enough that they could not interact, suggesting that a lack of interactions contributes to an increased death rate in addition to single-cell-level causes of damage. [86,87] The authors concluded that systemic aging is more important than cellular aging, especially because a healthy young cell with malfunctioning neighbors is more likely to die than an old or stressed cell with intact neighbors. [86] Tissue disruption as the "driver" of increased cell-to-cell variation in aging Thus, aging seems to be a phenomenon involving impaired intercellular interactions rather than one produced by cellular defects per se.…”
Section: The Tidis Theory Is Consistent With Lifetime Cancer Risksmentioning
confidence: 99%
“…We explained this observation with cooperative factors, which were carried by the flow toward the outlet. Cooperative factors are known to promote cell survival (19)(20)(21)(22)(23)(24)(25)(26), cardioprotection (21,22), and angiogenesis (22,23), and cells failing to receive the necessary factors from the neighboring cells go through apoptosis (32). Motivated by these results, we developed an analytical model to describe the death of cells that communicate via diffusive cooperative factors in a flowing environment.…”
Section: Discussionmentioning
confidence: 99%
“…Such biophysical extensions have been investigated experimentally (19) and theoretically (20) to understand how failure propagates through tissues, as mediated by the loss of diffusing cooperative factors. These cooperative factors could be cytokines (e.g., interleukin 15), growth factors (e.g., epidermal growth factor), survival factors (e.g., insulin-like growth factor 1), and antioxidant enzymes (e.g., superoxide dismutase 3) (21-29) diffusing across cells.…”
Section: Introductionmentioning
confidence: 99%
“…The main idea is that in a biophysically realistic interdependence network, the structure of connections between the nodes are determined by the exchange of various types of goods and signals, as mediated by diffusion and circulatory flow. Therefore, the transport system within an organism (by virtue of being a proxy for the interdependency between functional body components) will govern how it fails [15][16][17]. We will argue that the qualitative differences in the mortality curves may be due to (a) the structure of the interdependence network and (b) the type of goods exchanged through the network.…”
Section: Introductionmentioning
confidence: 99%